Eksistensi Ritel Tradisional Di Tengah Keberadaan Ritel Modern Di Kota Padangsidimpuan - Ian Ian Alfian; Erpiana Siregar (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2022)
This study aims to determine the existence of traditional retail in the midst of the existence of modern retail in the city of Padangsidimpuan and to determine the role of the government in increasing the existence of traditional retail in the midst of the existence of modern retail in the city of Padangsidimpuan. This type of research is descriptive qualitative research by interviewing traditional retailers and local governments. The results show that traditional retailers have different perceptions after modern retailers have stood around their businesses. Seven out of ten respondents have a negative perception while the other three people have a perception that there is no perceived impact. The government's role in this case is Cooperatives, Micro, Small and Medium Enterprises (MSME), and the Trade Office has given attention and has not ignored traditional retail traders. Traders receive capital assistance and offer to shift their business if their business cannot survive and are then given skills training.